2018
DOI: 10.1021/acs.orglett.8b03757
|View full text |Cite
|
Sign up to set email alerts
|

Direct and Asymmetric Nickel(II)-Catalyzed Construction of Carbon–Carbon Bonds from N-Acyl Thiazinanethiones

Abstract: A wide array of new N-acyl thiazinanethiones are employed in a number of direct and enantioselective carbon-carbon bond forming reactions catalyzed by nickel(II) complexes. The electrophilic species are mostly prepared in situ from ortho esters, methyl ethers, acetals, and ketals, which makes the overall process highly efficient and experimentally straightforward. Theoretical calculations indicate that the reactions proceed through an open transition state in a S N 1-like mechanism. The utility of this novel p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

5
3

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 35 publications
0
18
0
Order By: Relevance
“…Direct and Ni II -catalyzed addition of N-azidoacetyl thioimides to trimethyl orthoformate Our experience from the carbonÀcarbon bond-forming reactions of N-propanoyl thioimides indicated that the 6-membered thiazinanethione was slightly more selective and active than the 5-membered thiazolidinethione counterpart. [6] Unfortunately,w ew ere unable to synthesize the corresponding N-azidoacetyl-1,3-thiazinane-2-thione. The use of both azidoacetic acid and 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide (EDC) as ac oupling agento ra zidoacetyl chloride and triethylamine at 0 8Cu nder conditions previouslyd escribed led to a complexm ixture and no presence of the desired product.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Direct and Ni II -catalyzed addition of N-azidoacetyl thioimides to trimethyl orthoformate Our experience from the carbonÀcarbon bond-forming reactions of N-propanoyl thioimides indicated that the 6-membered thiazinanethione was slightly more selective and active than the 5-membered thiazolidinethione counterpart. [6] Unfortunately,w ew ere unable to synthesize the corresponding N-azidoacetyl-1,3-thiazinane-2-thione. The use of both azidoacetic acid and 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide (EDC) as ac oupling agento ra zidoacetyl chloride and triethylamine at 0 8Cu nder conditions previouslyd escribed led to a complexm ixture and no presence of the desired product.…”
Section: Resultsmentioning
confidence: 99%
“…[1][2][3] In this context,E vans [4] and Shibasaki [5] have convincingly established that both thiazolidinethione and azaindoline are suitable scaffolds to carry out direct and highly enantioselective aldol reactions catalyzed by chiral nickel(II) and copper(I) complexes, respectively.I nspired by such studies, we have recently reported that simple N-propanoyl-1,3-thiazinane-2-thione is av aluable platform from which to carry out direct and enantioselective carbonÀcarbon bond formingr eac-tions with ap lethora of cationic reagents using 1-5 mol %o f robust and easyt oh andle [(R)-DTBM-SEGPHOS]NiCl 2 . [6] Particularly,t he direct addition to trimethyl orthoformatea ctivated by TESOTf produces as ingle enantiomer of the corresponding adduct in 90 %y ield (Scheme 1A). Furthermore, formere vidence on similar reactions based on chiral N-acyl 1,3-thiazolidine-2-thiones catalyzed by (Me 3 P) 2 NiCl 2 indicated that the Nazidoacetyl counterpart was particularly suitable to provide highly stereocontrolled transformations (Scheme 1B), [7] which resultedi nb eing especiallya ppealing due to the well-known instability of metal enolates from those substrates.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, Shibasaki described a related enantioselective aldol addition of α‐sulfanyl 7‐azaindolinylamide catalyzed by a copper(I) complex,, whereas Aoki has recently reported that direct aldol reactions of a protected dihydroxyacetone with aromatic aldehydes catalyzed by zinc complexes containing histidine produce syn aldol adducts with good yields and enantioselectivities . In view of the lack of methods to prepare anti glycolate adducts and taking advantage of our experience with stoichiometric reactions of titanium(IV) enolates with acetals, and direct and highly stereoselective carbon‐carbon bond forming reactions from chiral N ‐acyl‐1,3‐thiazolidene‐2‐thiones catalyzed by nickel(II) complexes,, we envisaged that Lewis acid‐mediated glycolate aldol‐like additions to dialkyl acetals might proceed in a highly efficient manner. Importantly, such an approach was supported by the high yields and diastereomeric ratios achieved in the direct addition of N ‐azidoacetyl‐4‐isopropyl‐1,3‐thiazolidine‐2‐thione to dialkyl acetals promoted by 2–5 mol‐% of (Me 3 P) 2 NiCl 2 , a commercially available and easy to handle complex (Scheme ) .…”
Section: Introductionmentioning
confidence: 84%
“…In 2019, Urpi and co-workers reported the transamidation of N-acyl-1,3-thiazinane-2-thiones with amines in the presence of DMAP under metal-free conditions in excellent yields (Scheme 25). 51 Notably, various enantiopure N-acyl- This document was downloaded for personal use only. Unauthorized distribution is strictly prohibited.…”
Section: Scheme 24 Ytterbium-catalyzed Transamidation Of N-acyloxazolmentioning
confidence: 99%